The Family Strategy for Purple – Comparing the Methods of Andronikos I and Alexios I Komnenos of Constructing Imperial Power - Lachowicz, Paweł (Studia Ceranea, 2019)
In this paper I would like to concentrate on strategies and methods that were guiding Alexios I and Andronikos I of the Komnenos dynasty during the process of gaining and consolidating their power in the Byzantine Empire. Between these two emperors, who belonged to the same family, there exist many analogies in the way of carrying out a coup and constructing the authority based on a group of faithful aristocrats. It is crucial to highlight the active family politics which characterized both the emperors, as it was the main strategy aimed at ensuring the durability of the freshly acquired power. Between Andronikos’ and his grandfather’s coups passed almost exactly one hundred years. The completely different social and political situation of the Byzantine Empire in the late 12th century forced Andronikos to take a different approach. The most striking change was in the way of eliminating potential threats from the circles of Constantinopolitan aristocracy, especially when it comes to his relatives. Such a comparative analysis leads to some important observations concerning the social changes in the late 11th and 12th centuries, as well as mechanisms of seniority and precedence of power in the Komnenos family.